Editorial - Deniz EVCİK (Archives of Rheumatology, 2011)
Dear Readers of the Turkish Journal of Rheumatology, We are just about to introduce you to the new issue of the Turkish Journal of Rheumatology (TJR). Many thanks to our authors, reviewers, readers and Bayçınar Medical Publishing for their valuable contribution. The Annual European Congress of Rheumatology was held between the 25 and 28 of May 2011 in London. We would like to inform you that Professor Maurizio Cutolo was elected as the president of EULAR. The Turkish League Against Rheumatism and TJR attended as exhibitors with a stand in the EULAR Village. The visual presentations enhanced the awareness of our organization and the Journal. We hope these ongoing efforts will enable us to join new research fields with the collaboration of others in related disciplines. Once more, let me remind you of the significance of citations of the TJR, particularly with articles published in the last three years. It will both strengthen the scientific aspects of the journal and provide valuable contributions to be indexed in PubMed in the future. With my best regards Prof. Dr. Deniz Evcik Editor